Carbon–Fluorine Reductive Elimination from Nickel(III) Complexes. Issue 24 (11th May 2017) - Lee, Heejun; Börgel, Jonas; Ritter, Tobias
Abstract: We report a C−F reductive elimination from a characterized first‐row aryl metal fluoride complex. Reductive elimination from the presented nickel(III) complexes is faster than C−F bond formation from any other characterized aryl metal fluoride complex. Abstract : Fast and facile : Facile C−F reductive elimination from an arylnickel(III) fluoride complex is reported. The C−F bond reductive elimination from nickel(III) complexes presented herein is faster than the C−F bond formation from any other characterized aryl metal fluoride complex.